EQUAL STATUS BEFORE THE LAW BY INDIGENOUS PEOPLES IN ORDER TO IMPROVE THE QUALITY OF LIFE IN SOCIETY, NATION AND STATE: KESAMAAN DERAJAT DI HADAPAN HUKUM OLEH MASYARAKAT ADAT GUNA MENINGKATKAN KUALITAS KEHIDUPAN BERMASYARAKAT BERBANGSA DAN BERNEGARA - Rahmat, Doris; Daniswara, Widya (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
The utilization of the Nagari Customary Court is actually important because it is needed by the customary law community. In fact, it is the customary law community that knows and understands the historical aspects and the ins and outs of the lineage, environment and local culture. Therefore, this research seeks to find an optimal model of utilization of the Nagari Customary Court. How is equal status before the law by indigenous peoples in order to improve the quality of life in society, nation and state. This research is a socio-legal research that uses a qualitative approach. The data used in the research are primary and secondary data. The data collection method is through literature study and interviews. Therefore, the articles of Pancasila that regulate equal rights and justice also apply to indigenous peoples, and must also be perceived through philosophical, juridical and sociological perspectives. Indigenous Peoples according to Jawahir Thontowi is a group of citizens who have genealogical ancestors in common, live in a place, have a common goal of living within the framework of values and norms, still enforce a binding Adat system, led by the head of Adat, coordinate the administration of power and the existence of dispute resolution institutions in the community.